Raiz de roça: empoderamento feminino e capital social na agricultura familiar - Hanzen , Márcia (2021)
This thesis investigated how the participation of female farmers in the Family and Ecological Farmers Association of Medianeira - AAFEMED, contributes to increased empowerment and social capital. In this context, empowerment and social capital as an extension of freedom to choose and to act over the resources and decisions that affect their own lives, is associated with gender issues, of the female family farmer and of her standpoint. This was an exploratory study with a cross-section in 2020, without considering the evolution of the data over time. The primary data were collected by means of questionnaires given to 37 female farmers that volunteered to participate in the study. The first part surveyed the profile of these female farmers and the second part surveyed the extent that social capital, economic, social and personal indicators contributed to empowerment and improvements that occurred during this study. The data were treated as percentages and analysed descriptively. In addition, a documentary was elaborated with 11 female farmers on the subject which, after being edited, was made accessible through a code (QRcode) to complement the topic. The results indicated that participation in AAFEMED added greater personal empowerment (57%), economic empowerment remained the same for 59% of the interviewees and for social empowerment there was an increase for 47% while for 53% of the interviewees it remained unchanged. There was no indication of worsening in any of the indicators analysed in any of the dimensions of empowerment or social capital. For 67% of the female farmers there were satisfactory and very significant improvements in the dimensions that build empowerment and social capital, similarly for 52% of them these results are linked to the 14 years of work of AAFEMED. All indicators analysed showed that indeed, AAFEMED has contributed, mainly to the personal empowerment and increased social capital of the female rural members.